A bibliometric analysis of m-learning from topic inception to 2015. (2019) - Elaish, Monther M.; Shuib, Liyana; Ghani, Norjihan Abdul; Mujtaba, Ghulam; Ebrahim, Nader Ale
Mobile learning is a promising and widely adopted mode of education nowadays. However, to the best of our knowledge, there have been no studies that have investigated publications on the use of mobile learning in the Thomson Reuters Web of Science (WoS) through bibliometric analysis. This study aims to provide readers with statistical information to obtain a deep understanding of this domain. The results show that 3087 mobile learning publications have been published since 1982. As a result, the study has compared and determined the possible ways for researchers and authors to improve the citation rate of their publications on m-learning and to gain a deeper understanding of the field of mobile learning by studying the number of publications and country, the number of authors, the keywords, the number of references, the number of pages, the journal, the authors' publications, and the number of citations. Additionally, other bibliometric results are discussed.